The Impact of Augmented Reality on Consumer Engagement and Brand Loyalty - Zakiyya Tunnufus; Dini Arifian; Furniawan Furniawan; Dede Suharna; Pardomuan Pardosi (Journal Markcount Finance, 2024)
In today's digital era, Augmented Reality (AR) technology is increasingly gaining attention as an innovative tool in marketing and consumer experience. AR offers interactive experiences that combine virtual elements with the real world, giving consumers new ways to interact with goods and brands. This study aims to determine how the use of augmented reality (AR) technology impacts consumer engagement and brand loyalty. Specifically, this research wants to know how interactive experiences with AR affect consumers' level of engagement with a brand and how much that engagement contributes to the formation of brand loyalty. This research was conducted using a quantitative approach and was designed as a survey. AR apps from various brands deploy questionnaires to collect data. The goal of this questionnaire is to measure consumer engagement, user experience with AR, and brand loyalty.  Studies show that the use of augmented reality (AR) significantly increases consumer engagement with brands. Consumers say that interactive and immersive AR experiences make them more interested in the goods and brands. The study found that augmented reality (AR) technology increases consumer engagement and brand loyalty.